Resistensi Pendidikan Islam dalam Lintas Sejarah Indonesia - Hamzah, Syeh Hawib (IAIN Samarinda, 2011)
In Indonesia, there are challenges of the Islamic educational institutions. They are the first, internal challenge and the second, external challenge. The first is Human resource readiness and modernization of educational institutions. Islamic education in Indonesia such as Islamic Boarding Schools (pesantren), madrasah and Islamic schools have challenges to find an alternative to adapt to the development of civilization and modernization. The second challenges is the colonists who meddle in education policy in Indonesia. Islamic Boarding Scholls (pesantren) as holding of Islamic education in Indonesia has always received intimidation and discrimination in policies by the occupiers and even this policy go on in the early post-independence era to the new order that still feels unfair treatment to the institutions of Islamic education in Indonesia.